1988
DOI: 10.1126/science.2894075
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Characterized HLA DQ β Allele Associated with Pemphigus Vulgaris

Abstract: The inheritance of particular alleles of major histocompatibility complex class II genes increases the risk for various human autoimmune diseases; however, only a small percentage of individuals having an allele associated with susceptibility develop disease. The identification of allelic variants more precisely correlated with disease susceptibility would greatly facilitate clinical screening and diagnosis. Oligonucleotide-primed gene amplification in vitro was used to determine the nucleotide sequence of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(114 citation statements)
references
References 37 publications
10
103
0
1
Order By: Relevance
“…5). These findings are consistent with epidemiological studies showing a strong association of PV with HLA-DRB1*0402 (16) and HLA-DQB1*0503 (17,18) and a recent study from our group that identified Th cell responses to Dsg3 not only in PV patients but also in healthy carriers of the aforementioned PV-associated HLA class II alleles (22). These findings are in line with three independent studies demonstrating that Dsg3-specific TCC were restricted by HLA-DRB1*0402 (19,20,43).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5). These findings are consistent with epidemiological studies showing a strong association of PV with HLA-DRB1*0402 (16) and HLA-DQB1*0503 (17,18) and a recent study from our group that identified Th cell responses to Dsg3 not only in PV patients but also in healthy carriers of the aforementioned PV-associated HLA class II alleles (22). These findings are in line with three independent studies demonstrating that Dsg3-specific TCC were restricted by HLA-DRB1*0402 (19,20,43).…”
Section: Discussionsupporting
confidence: 92%
“…PV is associated with the HLA class II allele, HLA-DRB1*0402, particularly in Jewish patients (16), whereas DRB1*14/DQB1*0503 is prevalent in non-Jewish patients (17,18). Recent evidence suggests that these HLA class II alleles are involved in the presentation of Dsg3 peptides to autoreactive T cells in PV patients (19 -22).…”
Section: P Emphigus Vulgaris (Pv)mentioning
confidence: 99%
“…All 3 alleles were increased in Caucasian lupus nephritis patients; however, only DQP1.1 and DQPl .AZH were independently associated with nephritis. DR2,DQPl.AZH and DRw6,DQP1.9 are both quite rare in the normal Caucasian population (normal haplotype frequency -1% and -4%, respectively [ 12, and have been found to be associated with other autoimmune disorders: I .AZH with insulindependent diabetes mellitus (20,26) and 1.9 with pemphigus vulgaris (27,28). Residues 28 and 30 are at the bottom of the antigen-binding cleft, pointing upwards into the site, according to the hypothesized 3-dimensional model of the class I1 molecule (55); this implicates involvement of the first HVR in antigen interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, factor B and the second and fourth complement components (BF, C2, and C4A and C4B) have been detected by protein electrophoresis (15)(16)(17). Such molecular techniques as restriction fragment length polymorphism (RFLP) using MHC locus-specific complementary DNA (cDNA) probes, sequence-specific oligonucleotide (SSO) analysis, and direct sequencing of the polymorphic first domain have refined the analysis of class I1 allelic polymorphism as well as the identification of C4A and C4B gene deletions (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Estudos imunogenéticos demonstram aumentada incidência de HLA-DR4 (em judeus ashkenazi) ou DRw6 (em outros grupos étni-cos). [34][35][36] Cerca de 90% dos pacientes com PV tem envolvimento oral, e percentual que varia de 50 a 70% dos doentes inicia o quadro com lesões exulceradas em mucosa oral. 32 O PV afeta igualmente ambos os sexos 33 e ocorre principalmente em pacientes entre a quarta e a sexta décadas de vida; 37 todavia, podem ser afetados indivíduos de qualquer idade, incluindo crianças e recém-nascidos de mães com PV.…”
Section: Pênfigo Vulgar Introduçãounclassified